Lingual thyroid with absent thyroid gland in neck - Dhingra, Rachna; Singh, Gurbax; Kumar, Kuldeep; A. K., Vignesh; Singh, Pavail; Dhanoa, Simran (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Lingual thyroid is defined as an ectopic thyroid gland tissue located in the midline of the tongue base. Patients with lingual thyroid tissue usually present with symptoms such as dysphagia, choking, haemorrhage, dyspnea and occasionally life threatening airway obstruction. Lingual thyroid is a rare anomaly with an incidence of 1 in 3000 of the thyroid cases seen, with overall prevalence of 1 in 100,000. Here we presented a case with complaint of difficulty in swallowing and foreign body sensation throat. The intraoral examination showed spherical mass with 2 cm of diameter, covered with intact mucosa, located midline at base of tongue. She was diagnosed clinically as lingual thyroid and evaluated further. By proper transdisciplinary approach correct diagnosis can be made and patient can be managed. In present case, thyroid profile, USG neck and thyroid scintigraphy helped in diagnosis. Patient was managed medically with tablet levothyroxine which relieved her symptoms. Surgical management was not considered as patient improved with levothyroxine and surgical excision would have made patient further hypothyroid as there was no thyroid gland in neck.